Three Historical Problems in the Apologia Secunda of Athanasius - Van Nuffelen, Peter (Sacris Erudiri, 2005)
Abstract This paper addresses three problems in the early career of Athanasius of Alexandria (328-373). (1) Drawing on a passage from Sozomen (2.21.1-2), I argue that the re-integration of the Melitians in the Alexandrine Church most probably happened shortly after the return of Alexander of Alexandria from the council of Nicea (autumn 325). Apologia Secunda 59.2 does not offer conclusive evidence for the later date of late 327/early 328. Nor can the passage be taken to refer to a second session of the synod of Nicea. (2) The court of Dalmatius cannot be dated more precisely than between early 332 and summer 334. Moreover, there is no evidence that a synod of bishops was convoked in order to assist the judge in the form of a concilium. (3) In the years 337-341 only two synods of Antioch are certainly attested in the sources: the Dedication Council of January 341 and the council of early 339 during which Gregory was ordained. The council of Rome, which replied to a letter from the Dedication Council, must be situated after January 341, probably in late winter or early spring of 341. Scholars have often postulated the existence of many more councils, but there is no evidence for them, nor is their existence indispensable to explain the events. I also briefly re-assess the career of Pistos, the short-lived arian successor of Athanasius. He was probably ordained as bishop of Alexandria already before the council of Tyre (335) and while he and his Arian companions were still excommunicated by the church.